Pengembangan Game Multimedia Interaktif untuk Menstimulasi Perkembangan Nilai Agama dan Moral Tema Lingkunganku pada Anak Usia 5-6 Tahun di RA Nurul Hidayah Kota Jambi - Dwiyani, Ajeng Octatya; Sofyan, Hendra; Muazzomi, Nyimas (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This article aims to develop a learning medium in the form of an interactive multimedia game to stimulate the development of religious and moral values on the theme of my environment in children aged 5-6 years in RA Nurul Hidayah Jambi City. Development research (Research and Development/R&D) is this type of research. The development model used is ADDIE. The data collection method is a questionnaire. Data processing was carried out using quantitative data analysis and qualitative data. Research data was collected by distributing questionnaires to media experts, material experts, respondents, namely teachers at RA Nurul Hidayah Jambi city. The results of the research show that the media expert assessment obtained a percentage of 95.83% in the very good category and can be tested, the material expert assessment obtained a percentage of 83.3% in the very good category and suitable for use, and the results of the analysis of the respondent's perception questionnaire from 13 RA Nurul Hidayah teachers in Jambi City received a percentage of 95.6% in the very good category. From the results of this assessment, it shows that the interactive multimedia game learning media with the theme of my environment with the help of Microsoft PowerPoint is very effective in stimulating religious and moral values in children aged 5-6 years in RA Nurul Hidayah Jambi City and shows that this media is very suitable for use.